Members of the murine Pate family are predominantly expressed in the epididymis in a segment-specific fashion and regulated by androgens and other testicular factors - Damdimopoulos Anastasios E; Pujianto Dwi; Sipilä Petra; Turunen Heikki T; Björkgren Ida; Huhtaniemi Ilpo; Poutanen Matti (BMC, 2011)
Abstract Background Spermatozoa leaving the testis are not able to fertilize the egg in vivo. They must undergo further maturation in the epididymis. Proteins secreted to the epididymal lumen by the epithelial cells interact with the spermatozoa and enable these maturational changes, and are responsible for proper storage conditions before ejaculation. The present study was carried out in order to characterize the expression of a novel Pate (prostate and testis expression) gene family, coding for secreted cysteine-rich proteins, in the epididymis. Methods Murine genome databases were searched and sequence comparisons were performed to identify members of the Pate gene family, and their expression profiles in several mouse tissues were characterized by RT-PCR. Alternate transcripts were identified by RT-PCR, sequencing and Northern hybridization. Also, to study the regulation of expression of Pate family genes by the testis, quantitative (q) RT-PCR analyses were performed to compare gene expression levels in the epididymides of intact mice, gonadectomized mice, and gonadectomized mice under testosterone replacement treatment. Results A revised family tree of Pate genes is presented, including a previously uncharacterized Pate gene named Pate-X, and the data revealed that Acrv1 and Sslp1 should also be considered as members of the Pate family. Alternate splicing was observed for Pate-X, Pate-C and Pate-M. All the Pate genes studied are predominantly expressed in the epididymis, whereas expression in the testis and prostate is notably lower. Loss of androgens and/or testicular luminal factors was observed to affect the epididymal expression of several Pate genes. Conclusions We have characterized a gene cluster consisting of at least 14 expressed Pate gene members, including Acrv1, Sslp1 and a previously uncharacterized gene which we named Pate-X. The genes code for putatively secreted, cysteine-rich proteins with a TFP/Ly-6/uPAR domain. Members of the Pate gene cluster characterized are predominantly expressed in the murine epididymis, not in the testis or prostate, and are regulated by testicular factors. Similar proteins are present in venoms of several reptiles, and they are thought to mediate their effects by regulating certain ion channels, and are thus expected to have a clinical relevance in sperm maturation and epididymal infections.